THE CATEGORY OF TENSE OF VERBS (British Journal of Global Ecology and Sustainable Development, 2025)
This article examines the category of tense in verbs, analyzing its role in expressing time relations in different languages. The study explores how tense structures vary across linguistic systems and their impact on meaning and communication. Special attention is given to the distinctions between absolute and relative tenses, as well as the interrelation between tense, aspect, and mood. The findings highlight the significance of tense in structuring verbal expressions and its role in effective language use.